COMPARATIVE ANALYSIS OF GENETIC MATERIAL IN THE MERDEKA CURRICULUM AND CAMBRIDGE A LEVEL BIOLOGY: CONTENT, COMPETENCIES, AND COGNITIVE LEVELS APPROACH - Prasetyo, Nanda David (Journal of Learning on History and Social Sciences, 2025)
Objective: This study aims to comparatively analyze genetic material in the Merdeka Curriculum and Cambridge A Level Biology, focusing on the approach to content, built competencies, and cognitive levels based on Bloom's taxonomy. Method: The study was carried out through the analysis of official curriculum documents and reference textbooks for each curriculum. Results: The results showed that both curricula covered similar key themes of genetics, such as DNA structure and trait inheritance. However, the Merdeka Curriculum emphasizes more conceptual understanding and local contextualization with the dominance of the cognitive level of understanding (C2) and applying (C3). Meanwhile, Cambridge A Level presents material in a systematic and in-depth manner, demanding analytical and evaluative competencies (C4–C5), and integrating quantitative and statistical approaches. These differences reflect different philosophical orientations. The Merdeka curriculum focuses on meaningful learning and character building, while Cambridge A Level emphasizes scientific precision and advanced academic readiness. Novelty: The implications of this study lead to the importance of integrating approaches so that genetic learning becomes more balanced between academic depth and contextual relevance.